Social Determinants of Health and 90‐Day Mortality After Hospitalization for Heart Failure in the REGARDS Study - Sterling, Madeline R.; Ringel, Joanna Bryan; Pinheiro, Laura C.; Safford, Monika M.; Levitan, Emily B.; Phillips, Erica; Brown, Todd M.; Goyal, Parag (Journal of the American Heart Association, 2020)
Background Outcomes following heart failure (HF) hospitalizations are poor, with 90-day mortality rates of 15% to 20%. Although prior studies found associations between individual social determinants of health (SDOH) and post-discharge mortality, less is known about how an individuals' total burden of SDOH affects 90-day mortality. Methods and Results We included participants of the REGARDS (Reasons for Geographic and Racial Differences in Stroke) Study who were Medicare beneficiaries aged ≥65 years discharged alive after an adjudicated HF hospitalization. Guided by the Healthy People 2020 Framework, we examined 9 SDOH. First, we examined age-adjusted associations between each SDOH and 90-day mortality; those associated with 90-day mortality were used to create an SDOH count. Next, we determined the hazard of 90-day mortality by the SDOH count, adjusting for confounders. Over 10 years, 690 participants were hospitalized for HF at 440 unique hospitals in the United States; there were a total of 79 deaths within 90 days. Overall, 28% of participants had 0 SDOH, 39% had 1, and 32% had ≥2. Compared with those with 0, the age-adjusted hazard ratio for 90-day mortality among those with 1 SDOH was 2.89 (95% CI, 1.46-5.72) and was 3.06 (1.51-6.19) among those with ≥2 SDOH. The adjusted hazard ratio was 2.78 (1.37-5.62) and 2.57 (1.19-5.54) for participants with 1 SDOH and ≥2, respectively. Conclusions While having any of the SDOH studied here markedly increased risk of 90-day mortality after an HF hospitalization, a greater burden of SDOH was not associated with significantly greater risk in our population.